IMPLEMENTASI MANAJEMEN MUTU TERPADU PADA STANDAR PROSES DI SMP IT AR RAIHAN BANDAR LAMPUNG - Maharani, Estu (UNISAN JURNAL, 2024)
The purpose of this research is to implement integrated quality management in the standard process of SMP IT Ar Raihan Bandar Lampung. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographic location in the form of a location plan and environmental conditions, the school's vision, mission, strategy and motto as well as the condition of human resources at SMP IT Ar Raihan Bandar Lampung. Based on the results of the description that has been described, the Implementation of Integrated Quality Management focusing on customers on process standards at 12 Rantau Alai State Elementary School has been carried out to the fullest extent possible, this can be seen from: Customers who are satisfied with the services provided such as the services provided by TU to teachers, Integrated Quality Management respect for everyone on process standards All school members respect and appreciate each other, teachers always respect students, as well as students always respect teachers, Quality Management on process standards in continuous improvement have been carried out properly. The Principal of SMP IT Ar Raihan Bandar Lampung always makes improvements in all things, both improvements in terms of the learning process, namely facilities and infrastructure, Quality Management on Process Standards in leadership (leadership) has been carried out properly where the principal applies a system or democratic leadership style. Keywords: Integrated Quality Management, Process Standards.